Clustering in Cognitive Radio Networks: A Review - Sharma, Muskan; Garg, Sakshi; Thangjam, Sharmelee (International Journal of Computer Sciences and Engineering, 2025)
To overcome the drawback of underutilisation of the spectrum in wireless communication field, the Cognitive Radio (CR) technology came into existence, which permits the unlicensed or the Secondary Users (SU) to opportunistically use the available licensed spectrum when the licensed or the Primary User (PU) is not in use. The unlicensed user should not disrupt the working of the licensed user. To reduce the problem of shadowing and fading in CR, cooperative sensing was introduced in which many Cognitive Radio Users (CR Users) collectively report their decisions or data to the Fusion Center (FC) and it makes the final decision regarding the absence or presence of PU. In cooperative sensing, larger overhead is observed. Hence, clustering is one of the methods which reduces overhead. Clustering is a topology management system, in which the nodes are organized into logical groups known as clusters. It not only boosts the performance of the network but also achieves network scalability and stability, supports cooperative tasks, reduces the bandwidth requirement. This paper reviews the numerous clustering schemes, analyzes their characteristics and studies their performances.